Effect of reimplanting with Ralgro on performance and carcass characteristics of feedlot heifers - D. Simms; Gerry L. Kuhl; S. Tonn; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1983)
A field study was conducted to evaluate the effect of reimplanting, and of implanting technique, on the performance of yearling heifers. Daily gains of reimplanted, single implanted and non-implanted cattle averaged 3.00, 2.93 and 2.81 lb, respectively. Implanting Ralgro at the base of the ear produced a slight and not statically significant increase in again over the "old" site 1 to 2 in. from the base of the ear. Feed efficiency of the single implant heifers was 5.5% better than controls, with an additional 1.9% improvement due to reimplanting. Carcass characteristics were not materially influenced by implant treatment.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Reimplanting; Performance; Carcass; Heifers